Smart Urban Governance for Climate Change Adaptation - Thaler, Thomas (2021)
Climate change will affect the way cities work substantially. Flooding and urban heating are among the most tangible consequences in cities around the globe. Extreme hydro-meteorological events will likely increase in the future due to climate change. Making cities climate-resilient is therefore an urgent challenge to sustain urban living. To adapt cities to the consequences of climate change, new ideas and concepts need to be adopted. This oftentimes requires action from different stakeholder groups and citizens. In other words, climate adaptation of cities needs governance. Facilitating such urban governance for climate adaptation is thus a big and increasing challenge of urban planning. Smart tools and its embedding in smart urban governance is promising to help in this respect. To what extent can the use of digital knowledge technologies in a collaborative planning setting be instrumental in facilitating climate adaptation? This question entails visualising effects of climate adaptation interventions and facilitating dialogue between governments, businesses such as engineering companies, and citizens. The aim of this thematic issue is to explore how the application of technologies in urban planning, embedded in smart urban governance, can contribute to provide climate change adaptation. We understand smart urban governance in this context both in terms of disclosing technical expert information to the wider public, and in terms of supporting with the help of technologies the wider governance debates between the stakeholders involved. The contributions reflect this dual focus on socio-technical innovations and planning support, and therefore include various dimensions, from modelling and interacting to new modes of urban governance and political dimensions of using technologies in climate change adaptation in urban areas.